Etude comparative de la résistance à l’abrasion de trois fixatifs utilisés comme consolidant de techniques graphiques - Anne Laure Gautier (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This study aimed to compare the abrasion resistance of three fixatives commonly used in restoration of graphic works as consolidating graphics techniques. Two cellulose ethers were tested (hydroxypropylcellulose and methylcellulose) and a fixative made from animal organism, gelatin. This study shows the development of an abrasion machine. The level of abrasion was determined thanks to a glossmeter. The results have shown that the methylcellulose as the most satisfactory product.